The Factors That Influence The Behavior of Seeking Traditional Health Services in The Community of The Working Area of Bluto Public Health Centre - Sodik, Muhammad Ali; Aminah Raudatul Jannah (Journal of Global Research in Public Health, 2022)
We find more and more traditional health services. In Bluto District, Sumenep Regency, there are many traditional health services by traditional healers (hattra) and many people still visit. This study aims to determine the factors that influence the seeking behavior of traditional health services in the working area of ​​Puskesmas Bluto with a case control study design on 96 respondents who have visited traditional health services by Hattra and Nakestrad. The results of the study through statistical tests with the chi square test with an alpha value of 0.05 showed that several factors had a significant relationship, gender, age, education, attitudes, perceptions of healthy illness, perceptions of traditional medicine and subjective views with alpha values ​​<0.05. to traditional health services. In addition, several variables were found that showed no significant relationship with alpha values> 0.05, namely marital status, employment, income and knowledge.